Attachment of cells to basement membrane collagen type IV (The Rockefeller University Press, 1986)
Of ten different cell lines examined, three showed distinct attachment and spreading on collagen IV substrates, and neither attachment nor spreading was enhanced by adding soluble laminin or fibronectin. This reaction was not inhibited by cycloheximide or antibodies to laminin, indicating a direct attachment to collagen IV without the need of mediator proteins. Cell-binding sites were localized to the major triple-helical domain of collagen IV and required an intact triple helical conformation for activity. Fibronectin showed preferential binding to denatured collagen IV necessary to mediate cell binding to the substrate. Fibronectin binding sites of collagen IV were mapped to unfolded structures of the major triple-helical domain and show a similar specificity to fibronectin-binding sites of collagen I. The data extend previous observations on biologically potential binding sites located in the triple helix of basement membrane collagen IV.